Control and prediction of noise and ground vibrations generated by rock blasting - Dorneles, Felipe Tavares (2014)
Air blast and ground vibrations generated by rock blasting have become a major legal and technical problem, mainly due the growing of the cities to the neighborhood of mines and quarries. For many people, the main environmental impacts associated with mining are those generated by rock blasting, and there is a real risk in handling explosives since just around 20-30% of the explosives energy is used to fragment and throw the rock. But the effects of explosives can be precalculated and predicted quite accurately, according the regulations for the use of explosives which are meant to be such a safeguard against accidents. These rules or laws establish that it is necessary to carry out a risk analysis in order to determine, first, what size vibrations the environment will accept and second, how large a charge can be blasted at certain distance without exceeding that vibration or noise limits. This risk analysis has been made in the limestone mines of Caçapava do Sul involving a careful examination of the factors that can affect the blasting operations. At the same time, a mathematical model has been developed in order to reliably predict the noise and vibration levels for a determined distance in the vicinity of the blasting place.